EXPLORING THE HEALING WISDOM: A LITERATURE REVIEW OF MEDICINAL AYAHS IN ISLAMIC TEXTS - Sania Qazi; Hira Babar Rana (International Journal of Islamic and Complementary Medicine, 2026)
Islamic scripture has historically served as a source of guidance not only for spiritual practice but also for health and healing. This literature review examines Quranic verses (Ayahs) with explicit or implicit references to medicine and well-being, aiming to contextualize their significance in both classical and contemporary healthcare paradigms. A systematic literature search across primary Islamic sources, tafsir (exegesis), and modern academic databases was conducted. Ayahs were screened for references to physical, mental, and spiritual health, followed by thematic analysis and review of scholarly interpretations. Out of 342 potentially relevant Ayahs, 78 met inclusion criteria and were reviewed in detail, spanning 18 Surahs. Key themes included physical health (e.g., dietary guidance, hygiene), mental health (e.g., tranquility through remembrance of God), and spiritual health (e.g., reliance on divine healing). Classical scholars such as Al-Tabari and Ibn Kathir emphasized the theological context, while contemporary scholarship highlights their resonance with preventive medicine, holistic care, and psychosocial well-being. This synthesis demonstrates that Quranic teachings promote an integrated vision of health, underscoring the interplay between body, mind, and spirit. The findings support continued exploration of religious texts to inform culturally sensitive, ethical, and holistic approaches to modern healthcare.